2013
DOI: 10.1597/12-115
|View full text |Cite
|
Sign up to set email alerts
|

Role of Facial Artery Musculomucosal Flap in Large and Recurrent Palatal Fistulae

Abstract: Objective : Palatal fistulas are not uncommon after palatoplasty. Although there are currently many techniques that can be used to close large palatal fistulae, most of these procedures are usually cumbersome and mostly unreliable with high recurrence rates. The facial artery musculomucosal (FAMM) flap was described to circumvent these problems. The purpose of this study was to review our experience with the FAMM flap to reconstruct palatal fistulas, most of them being recurrent. Materials and Methods : A retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
(18 reference statements)
0
20
0
Order By: Relevance
“…Only the longest flap of 15 × 70 mm failed, as complete necrosis [11]. In another report by Shetty et al [17], an anterior fistula following dental cyst excision, which measured 1.2 cm 2 , was successfully closed with a superiorly-based FAMM flap. In contrast, our patient had intractable OAF with chronic infection following dental extraction that was previously closed with a palatal flap, unsuccessfully.…”
Section: Discussionmentioning
confidence: 99%
“…Only the longest flap of 15 × 70 mm failed, as complete necrosis [11]. In another report by Shetty et al [17], an anterior fistula following dental cyst excision, which measured 1.2 cm 2 , was successfully closed with a superiorly-based FAMM flap. In contrast, our patient had intractable OAF with chronic infection following dental extraction that was previously closed with a palatal flap, unsuccessfully.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2014) reported a higher rate of recurrence, 18% (4/22) when using the buccal flap for both primary and secondary palate fistula closures. Shetty et al (2013) conducted a retrospective analysis on FAMM flaps and reported no fistula recurrences (0/11) after fistula repair, suggesting that FAMM flaps are a reliable flap for larger, complicated defects. While these results are encouraging, future studies comparing outcomes of buccal and FAMM flaps by fistula size and location may improve the flap selection process.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, enoral myomucosal local axial flaps such as the Bozola flap, based on the buccal artery, or in case of medium‐sized defects the facial artery musculomucosal flap, commissure based buccal musculomucosal flap, and dorsally based buccal musculomucosal flap can be employed. The latter flaps have the advantage not to require facial artery dissection for similar flap sizes.…”
Section: Discussionmentioning
confidence: 99%